Family of single‐switch quasi‐resonant converters with reduced inductor size. Issue 10 (1st October 2014) - Sharifi, Saead; Jabbari, Masoud
Abstract : This study presents a family of single‐switch soft‐switching converters with 18 new topologies. The passive elements include two relatively small inductors and one resonant capacitor. The switch can be half‐wave or full‐wave which turns on and turns off at zero‐current switching (ZCS). The diode is turned off at ZCS and thus its reverse recovery problem is obviated. The converters operate at discontinuous conduction mode (DCM) and continuous conduction mode (CCM) depending on the load current. For the full‐wave switch, an almost constant switching frequency is attained at CCM. The presented experimental results from a 200 W/185 kHz laboratory prototype confirm the presented theoretical analysis. For this prototype, the switching frequency variation at CCM is only 70 Hz/W.